Palladium‐Boride Nanoflowers with Controllable Boron Content for Formic Acid Electrooxidation - Liu, Yi‐Ming; Miao, Bo‐Qiang; Yang, Han‐Yue; Ai, Xuan; Wang, Tian‐Jiao; Shi, Feng; Chen, Pei; Chen, Yu (Advanced functional materials, 2024)
The rational design of the electronic structure and elemental compositions of anode electrocatalysts for formic acid electrooxidation reaction (FAOR) is paramount for realizing high‐performance direct formic acid fuel cells. Herein, palladium‐boride nanoflowers (Pd‐B NFs) with controllable boron content are rationally designed via a simple wet chemical reduction method, utilizing PdII‐dimethylglyoxime as precursor and NaBH4 as both reductant and boron source. The boron content of Pd‐B NFs can be regulated through manipulation of reaction time, accompanying with the crystal phase transition from face‐centered cubic to hexagonal close‐packed within the parent Pd lattice. The obtained Pd‐B NFs exhibit increased FAOR mass and specific activity with increasing boron content, showcasing remarkable inherent stability and anti‐poisoning capability compare to commercial Pd and platinum (Pt) nanocrystals. Notably, the sample reacted for 12 h reveals high FAOR specific activity (31.5 A m−2), which is approximately two times higher than the commercial Pd nanocrystals. Density functional theory calculations disclose that the d‐sp orbital hybridization between Pd and B modifies surface d‐band properties of Pd, thereby optimizing the adsorption of key intermediates and facilitating FAOR kinetics on the Pd surface. This study paves the way toward the utilization of metal boride‐based materials with simple synthesis methods for various electrocatalysis applications. Palladium‐boride nanoflowers (Pd‐B NFs) with controllable boron content and crystal phase transition from face‐centered cubic to hexagonal close‐packed are synthesized by a simple wet chemical reduction method. Pd‐B NFs obtained after 12‐h reaction possess modified Pd surface electronic structure by d‐sp orbital hybridization, thus perform the optimized adsorption behavior of key intermediate, demonstrating remarkable performance towards formic acid electrooxidation.